(untitled) (Semiárida, 2019)
The essential oils (EOs) from 5 native aromatic plants from La Pampa, Argentina, were obtained by hydrodistillation and tested for repellency on Tribolium castaneum Herbst. adults. All tested EOs showed high repellency activity at the highest concentration established (0.3 mg.cm2). The EOs from Baccharis spartioides and Helianthus petiolaris were the most efficient, showing higher repellency when compared to the standard positive control (DEET). At 3x101 mg.cm2, B. spartioides and H. petiolaris showed 95% and 92.2% of repellency respectively. The EOs chemical composition was then analyzed by Gas chromatography–mass spectrometry (GCMS) and the first report of H. petiolaris EO composition is presented. Finally, in order to assess repellency activity in simulated “field conditions”, pest behavior was evaluated in treated flour. In presence of H. petiolaris EO, 90% of the insects left the grain, while B. spartioides induced an 81% of emigration. To maximize the yields in repellent production, a blend using commercial lemon EO was proposed. The results obtained show a significant difference after 24 h of treatment, were the repellency of the blend persisted in contrast with pure EOs. These findings present the B. spartioides and H. petiolaris EOs blends as promising alternatives to control T. castaneum in stored grains.